Analisis Kekuatan Drawbridge Compact Indexer Pabrik Kelapa Sawit dengan SolidWorks Simulation - Kurniawan, Sandi (Journal of New Energies and Manufacturing, 2023)
One of the ways to increase the efficiency of palm oil mills is in the sterilization process with the development of a compact indexer system in the cage transfer process. In the compact indexer system, a drawbridge is added to the transfer carriage structure as a connecting bridge with the sterilizer and tipper. In the improvement of transfer carriage, the drawbridge design must be able to support the load from the cage when it rests on the drawbridge. Based on the case that occurred at PT. XYZ in West Kalimantan, there was damage to the drawbridge structure which may be caused by operator error in operating the system or calculation error in design. So related to the design process design in this study, the analysis was carried out to determine the maximum stress on the drawbridge when resisting static loading by the cage and the value of safety factor the drawbridge design. The analysis was carried out using the static simulation feature in SolidWorks to determine the resistance and strength of the structure to the given static loading, because in the previous design process only used AutoCad 2D and no loading simulation was performed. The results of the analysis is that the maximum von Mises Stress value on the drawbridge structure due to static loading is 1,02 x 108 N/m2 which causes the structure to deform by 0.222 mm. The deformation that occurs is an elastic deformation because the von Mises Stress is below the yield strength of ASTM A36 material of 2,5 x 108 N/m2. Based on 7 static loading simulation positions, it was found that the drawbridge did not meet the safety factor. The drawbridge design does not meet the safety factor in the first simulation with a safety factor value of 0.8 and the sixth simulation with a safety factor value of 0.85 and the seventh simulation with a safety factor value of 0.92. The part that needs improvement to increase the safety factor of the drawbridge is the end of the drawbridge which rests on the sterilizer rail.